1993
DOI: 10.1002/eji.1830230140
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of CD14 in stimulation of cytokine production by uronic acid polymers

Abstract: In this study the molecular mechanisms behind the stimulatory activities of the uronic acid polymers poly mannuronic acid (poly M), high M alginate and oxidized cellulose (C60XY) were investigated and compared with lipopolysaccharide (LPS). The cytokine-inducing abilities of the uronic acid polymers and LPS were examined on CD14-positive human monocytes and CD14-negative U373 astrocytoma cells. It was found that LPS induced monocytes and U373 cells to produce tumor necrosis factor (TNF) and interleukin(IL)-6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
1
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(115 citation statements)
references
References 32 publications
2
109
1
3
Order By: Relevance
“…Soluble alginate rich in mannuronic acid (>86%) is able to induce TNF in monocytes through mechanisms involving CD14 [30] TLR2 and TLR4 [31]. Recently it was demonstrated that purified alginate rich in guluronic acid as used currently, did not activate TLRs [32].…”
Section: Cd11b Cd18 or Cd11c Blockagementioning
confidence: 99%
“…Soluble alginate rich in mannuronic acid (>86%) is able to induce TNF in monocytes through mechanisms involving CD14 [30] TLR2 and TLR4 [31]. Recently it was demonstrated that purified alginate rich in guluronic acid as used currently, did not activate TLRs [32].…”
Section: Cd11b Cd18 or Cd11c Blockagementioning
confidence: 99%
“…The receptor for mannuronan on human monocytes is CD14 [8], which also is a functional receptor for LPS [10]. CD14 may exist as a soluble molecule (sCD14) and is thought to mediate LPS effects on cells that do not express the membrane form [27].…”
Section: Discussionmentioning
confidence: 99%
“…It also binds to membrane CD14 [8,9], and requires serum or lipopolysaccharide-binding protein (LBP) for TNF production [8,9]. The CD14 receptor also binds LPS and mediates LPS effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…(Wright et al, 1990;Espevik et al, 1993;Haziot et al, 1996;Weidemann et al, 1997;Dziarski et al, 1998;Ingalls et al, 1999). CD14 also involves in TLR2-dependent initiation of immune response (Schroder et al, 2003), however, depending on the nature of the ligand, the presence of which is not absolutely required by all TLR2 complexes for signaling activity (Jiang et al, 2005).…”
Section: Tlr2mentioning
confidence: 99%